2019
DOI: 10.4293/jsls.2018.00076
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Hysterectomy Outcomes: Hospital vs Ambulatory Surgery Center

Abstract: Background and Objective:Compare operative outcomes of laparoscopic hysterectomy in an outpatient hospital setting versus freestanding ambulatory surgery center.Methods:Retrospective cohort study of two groups in an outpatient hospital surgery department and freestanding ambulatory surgical center, both serving the Washington, DC area. Women, 18 years or older, who underwent laparoscopic hysterectomy for benign conditions in an outpatient hospital setting between 2011 and 2014 (n = 821), and at an ambulatory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Although there are no studies specifically addressing TVH at ASCs, it has been shown that complex gynecologic surgery, including TLH, can be safely performed at ASCs. 16,17 It is worth noting that all cohorts cited a lack of access as a reason they do not use ASCs as opposed to discomfort with ASCs for TVH surgery. Geographical location did play a role, with a significantly higher portion of surgeons from the Mid-Atlantic reporting using an ASC.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no studies specifically addressing TVH at ASCs, it has been shown that complex gynecologic surgery, including TLH, can be safely performed at ASCs. 16,17 It is worth noting that all cohorts cited a lack of access as a reason they do not use ASCs as opposed to discomfort with ASCs for TVH surgery. Geographical location did play a role, with a significantly higher portion of surgeons from the Mid-Atlantic reporting using an ASC.…”
Section: Discussionmentioning
confidence: 99%
“…7 An important point is different reports of early years of laparoscopy with longer procedures in comparison to the open method. 20 Three characters are regarded for learning curve assessment including the duration of surgery, rate of complications, and the number of conversions to open surgery. In a study, in the learning curve of laparoscopic hysterectomy, the first 10 procedures were done in a mean time of 180 minutes and decreased to 75 minutes in the 90-100th patients.…”
Section: Operation Timementioning
confidence: 99%
“…Con el perfeccionamiento del abordaje mínimamente invasivo, se han publicado estudios que muestran que la vía laparoscópica podría acompañarse de una política de egreso temprano (primeras 12 a 24 horas de la histerectomía) dada la seguridad de este procedimiento. Por ejemplo, MacKoul et al comparan dos instituciones en las que se dio salida temprana, una con manejo ambulatorio con alta temprana en el 98% de las pacientes y otra con hospitalización con salida temprana en 88%, sin diferencia en la frecuencia de complicaciones 7 . Estas observaciones han llevado a un incremento de la frecuencia del alta temprana en pacientes con histerectomía laparoscópica de un 13% en el 2008 a un 57% en el 2014 en centros quirúrgicos ambulatorios de Estados Unidos 8 .…”
Section: Introductionunclassified